ENGLISH SPEAKING COUNTRIES - Abdumoʻminova Sojida; Zoirova Lola; Mardonova Marjona (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: English is one of the most widely spoken languages in the world and is used as an official or second language in many countries. The spread of English is related to historical, cultural and economic factors. This article provides detailed information about English-speaking countries, their history, culture, and the role of the English language.